Makam “Puyang Mengkedum Sakti” sebagai Tokoh Penyebaran Islam di Kabupaten Lahat - Cyndy Felisya; Hudaidah Yusuf (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the role of the Tomb of Puyang Mengkedum Sakti as a historical and cultural symbol in the spread of Islam in Lahat Regency, South Sumatra. The main issue addressed is the lack of documentation and public understanding of Puyang Mengkedum Sakti’s contribution to the Islamization process in the region. The objective of the research is to identify the historical and da’wah values embedded in the tomb site and to understand the figure’s role in the local spread of Islam. A qualitative method was employed, using data collection techniques such as observation, in-depth interviews, and literature study. The results indicate that Puyang Mengkedum Sakti is a revered figure known for spreading Islamic teachings through local cultural adaptation and religious education. His tomb now serves as a pilgrimage site and a symbol of Islamic identity for the Lahat community.